KONSELING INDIVIDUAL UNTUK MENINGKATKAN KEDISIPLINAN SISWA DI SEKOLAH DENGAN CARA PENDEKATAN BEHAVIOUR REALITA DI SMP PGRI 3 BANJARMASIN - Nur Latifah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2017)
The purpose of this study was to determine kedisplinan eighth grade students at SMP PGRI 3 Banjarmasin before and after behavior techniques reality in individual counseling services program, as well as to determine the effectiveness of counseling techniques in improving discipline in class VIII SMP PGRI 3 Banjarmasin. This research is a quantitative method of experiment, the research was conducted in SMP PGRI 3 Banjarmasin. The population in this study were students in class VIII, amounting to 22 people. The research sample is obtained by using purposive sampling technique which consists of 4 people. The research instrument used was peralukan material in the form of "reality pedomen behavior techniques to improve student discipline" and the data collection instruments in the form of a scale measuring levels of discipline behavior. Data analysis techniques formula T-Test showed thit amounted to 6.035 between the percentage of students disciplined behavior before and after individual counseling with ttab value of 2.920, which means there is a difference. Based on the research that has been carried out, there are a few things to note for users of guidelines behavior approaches reality, further research and schools. while it is still subjective nature of this study because in the process of individual counseling or implementation of this experiment, the researchers also act as counselors.